Akuntabilitas Sosial dalam Praktik: Penguatan Peran Masyarakat dalam Pengelolaan Keuangan Desa - Pramudya, Arya Ananta; Koeswara, Hendri; Aromatica, Desna (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2025)
The Kepenuhan Hulu Village Government has successfully encouraged the community to participate actively in deliberation forums to convey information about accountability and receive feedback from the community. This indicates the existence of social accountability practices in financial management in Kepenuhan Hulu Village. This study examines how social accountability in village financial management is implemented using the Social Accountability theory of Grandvoinnet et al. The results show that social accountability in financial management in Kepenuhan Hulu Village is built through active community involvement and the village government's commitment to creating transparent and participatory governance. Social accountability is manifested in deliberation forums such as hamlet deliberations, village deliberations, and village development planning deliberations. These forums have become a space for the community to express aspirations and determine the direction of village development. The findings of this social accountability study have implications for strengthening accountability in village financial management by optimizing the deliberation mechanism regulated by the regulation to be more inclusive and based on real community needs. With a clear commitment from the village government to meeting community demands and needs, this social accountability approach can serve as a reference for strengthening more transparent village financial management.